Provision Of Beer Dregs and Rejected Bread On Production and Milk Fat In Jabung Agro Trade Cooperatives Malang Regency - Dewi Setiyoningsih; M. Gandul Atik Yuliani; Miyayu Soneta Sofyan; Sri Hidanah (Journal of Applied Veterinary Science And Technology, 2022)
Background: In the maintenance of dairy cows, feed must be considered because it can affect the productivity of dairy cows, including milk production and quality. Purpose: to determine the effect of giving beer dregs and rejected bread on milk and milk fat production. Methods: The method used is primary data collection, recording milk and milk fat production for two weeks to determine the difference between giving beer dregs and rejected bread to milk and milk fat production. Results: The results showed that providing beer dregs and rejected bread to dairy cows could increase milk production and fat content. Cows as control treatment had fat content with an average of 3.95%, and cows given beer dregs had fat content with an average of 4.61%. Cows given rejected bread had fat content with an average of 5.01%. For the milk production of dairy cows as a control treatment, an average of 11.8 liters/day, the average production of dairy cows fed with beer dregs is 13.3 liters/day, and the production of dairy cows given rejected bread is an average of 14 liters/day. Conclusions: The conclusion that can be obtained is that the provision of beer dregs and rejected bread as additional feed has a significant effect on increasing milk production and milk fat content of dairy cows.